(untitled) (Canadian Rheumatology Today, 2025)
Spondyloarthritis refers to a group of inflammatory rheumatic diseases characterized by shared clinical features, such as inflammatory involvement of the axial skeleton, a specific pattern of peripheral joint involvement (usually asymmetric mono- or oligoarthritis, predominantly involving the lower extremities), enthesitis, and dactylitis. Common extra-musculoskeletal manifestations include acute anterior uveitis, psoriasis, and inflammatory bowel disease (Crohn’s disease and ulcerative colitis). Axial spondyloarthritis (axSpA) denotes the subset of spondyloarthritis with predominant involvement of the spine and sacroiliac joints. The term axSpA encompasses both non-radiographic disease (no definite structural damage on X-rays of the sacroiliac joints) and radiographic disease, which has historically been referred to as ankylosing spondylitis. In clinical practice, these entities represent a spectrum. axSpA may initially present without X-ray changes and in some patients, may later progress to classic ankylosing spondylitis. In this article, we will review the approach to diagnosing (versus classifying) axSpA and examine the role of imaging modalities in diagnosing axSpA and distinguishing it from common mimics.